Properties of Soil and Plant Biodiversity in the Landslide Prone Area of Nikola Oya, Rattota - Katupotha, K.N.J.; Kumara, Sumanajith (My University, 2013)
Attached

The study analysed surface and sub-surface soils, underlying rocks, vegetation types and relief in the massive landslide prone area at Nikola Oya. Tha influence of soil properties and identification of dominant, original and effective plant species on landslide occurrences were undertaken by field work on December, 2012; July and August 2013. Other relevant data and information were collected from maps, images and through formal and informal discussions with affected persons and officials. The study on physio-chemical parameters of soils in the Nikola Oya landslide area has revealed undifferentiated charnockitic biotite gneisses; Quartzite and Marble are the dominant rock types in the area. Likewise, Red-yellow podzolic and wet mountain soils as well as Red-yellow podzolic and immature brown loams appear in this area. A salient feature of the area is the steep, hilly and rolling terrain. The vegetation cover of the Nikola Oya basin comprises Sub Montane Forests and Moist Monsoon Forests, but the vegetation in the landslide affected area is characterized by poor-nutrient content due to the disturbance of plant biodiversity and the deficiency of managing nutrients like Nitrogen. Such nutrients fixing plant species like Gliricidia cover parts of the landslide prone but it was found that diverse species with dense vegetation would be more appropriate. Precipitous slopes and absence of a dense vegetation cover are not the only reason for landslide occurrences in the region. Other environmental factors such as heavy rainfall during the monsoon periods as well as the nature of soil have contributed to slope failure, together with production clammy soils by microbial. Thus, the study has identified the multitude of factors including microbiology responsible for landslides in the area and highlighted the need for urgent short and long term mitigatory measures such as relocation of affected persons and reforestation of this environmentally fragile area.
Keywords: Environmentally fragile are; Plant biodiversity; Microbial; Properties of soils Landslides